2020
DOI: 10.1186/s13020-020-00359-1
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for anti-Alzheimer’s disease: berberine and evodiamine from Evodia rutaecarpa

Abstract: Alzheimer's disease (AD) is one of the most common diseases in elderly people with a high incidence of dementia at approximately 60-80%. The pathogenesis of AD was quite complicated and currently there is no unified conclusion in the academic community, so no efficiently clinical treatment is available. In recent years, with the development of traditional Chinese medicine (TCM), researchers have proposed the idea of relying on TCM to prevent and treat AD based on the characteristic of multiple targets of TCM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 127 publications
(143 reference statements)
1
25
0
2
Order By: Relevance
“…TCM is generally a natural product after long-term clinical practice, with good safety and low toxicity. In addition, TCM is characterized by the use of multiple compounds, multiple targets, and multiple pathways of action, thus having certain advantages for complex diseases ( Fang et al, 2020 ). Thus, we assumed that the treatment of PR might be ascribed to the integrated effects of multiple compounds, rather than a single constituent.…”
Section: Discussionmentioning
confidence: 99%
“…TCM is generally a natural product after long-term clinical practice, with good safety and low toxicity. In addition, TCM is characterized by the use of multiple compounds, multiple targets, and multiple pathways of action, thus having certain advantages for complex diseases ( Fang et al, 2020 ). Thus, we assumed that the treatment of PR might be ascribed to the integrated effects of multiple compounds, rather than a single constituent.…”
Section: Discussionmentioning
confidence: 99%
“…Многочисленные исследования in vivo, проведенные за последнее время, показали нейропротекторное действие алкалоида хинолина -берберина [201]. Берберин ингибирует активность ВACE1 и АХЭ, снижает уровень АФК, повышает уровень глутатиона, препятствует апоптозу и улучшает когнитивные функции [202,203]. Внесение берберина в наноструктурированные липидные носители повысило его биодоступность и эффективность в эксперименте in vivo [204].…”
Section: потенциальные нейропротекторные препараты воздействующие одн...unclassified
“…BBR can be extracted from various plant families, including Annonaceae , Berberidaceae , Menispermaceae , and Papaveraceae [ 1 ]. Over the past decades, BBR has emerged as an important compound in traditional Chinese medicine because of its wide range of applications [ 2 , 3 ]. Numerous studies have demonstrated that BBR exhibits positive pharmacological effects in many diseases such as cancer [ 4 , 5 ], inflammation [ 6 ], bacterial infection [ 7 ], reperfusion injury [ 8 ], and non-alcoholic fatty liver (NAFL) disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%